The Effect of Ownership Structure and Audit Quality on Firm Performance - Angsoyiri, Dramani (Future Science / FSH-PH Publications, 2021)
The study examined the effect of ownership structure and audit qual-ity on firm performance of listed companies in Ghana. The research employed a quantitative research approach; secondary data was ex-tracted from various annual reports and financial statements of the selected companies. The target population was all 42 listed compa-nies on the Ghana Stock Exchange. The sample size was 20 companies selected from all industries. The study period was 2013-2018 re-sulted in 160 firm-yearly empirical observations. The study used re-turn on asset (ROA) and return on equity (ROE) as the performance measure. Ownership structure was measured using managerial own-ership and institutional ownership, audit quality was also measured with the auditor’s reputation, audit committee size and audit commit-tee independence. The control variables used were board size and firm size. The researcher found a weak positive correlation between institutional and managerial ownership and firm performance. More-over, there was a positive effect of audit quality on firm performance. It implies that the engagement of the services of the Big 4 audit firms has an incremental effect on firm performance. Audit committee size posited a positive effect on firm performance whereas audit commit-tee independence was seen to harm firm performance. Similarly, board independence showed a positive effect on ROE and a negative effect on ROA. Board size, however, indicated a positive effect on firm performance. The researcher recommended the pressing need of di-versifying shareholdings in firms as a sweetener to attract more skills and expertise among shareholders that can be tapped to enhance the performance of firms. However, managers should be protected from unnecessary shareholding meddling.